2011
DOI: 10.1093/carcin/bgr224
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the common regulators for hepatocellular carcinoma induced by hepatitis B virus X antigen in a mouse model

Abstract: Hepatitis B virus X antigen plays an important role in the development of human hepatocellular carcinoma (HCC). The key regulators controlling the temporal downstream gene expression for HCC progression remains unknown. In this study, we took advantage of systems biology approach and analyzed the microarray data of the HBx transgenic mouse as a screening process to identify the differentially expressed genes and applied the software Pathway Studio to identify potential pathways and regulators involved in HCC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 46 publications
5
61
0
1
Order By: Relevance
“…In contrast to the beneficial effects observed in the rodent liver fibrosis model, BMP7 expression is elevated in patients with chronic liver diseases, raising the question of species-specific effects of BMP7 (56,57). A recent study using a hepatitis B model of HCC in mice as well as human HCC samples confirmed up-regulation of BMP7 in cirrhotic and cancerous liver tissues (36). The same study also demonstrated increased cell viability, migration, and invasiveness in the hepatoma cell line Hep3B.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast to the beneficial effects observed in the rodent liver fibrosis model, BMP7 expression is elevated in patients with chronic liver diseases, raising the question of species-specific effects of BMP7 (56,57). A recent study using a hepatitis B model of HCC in mice as well as human HCC samples confirmed up-regulation of BMP7 in cirrhotic and cancerous liver tissues (36). The same study also demonstrated increased cell viability, migration, and invasiveness in the hepatoma cell line Hep3B.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, expression of the Bmp antagonist Gremlin2 (Grem2/Prdc) was significantly reduced in tamoxifen-treated Hnf4a F/F;AlbERT2cre mice. A recent study found elevated BMP7 levels in a hepatitis B mouse model of HCC and further identified elevated BMP7 in human cirrhotic liver and HCC samples (36). To assess whether the induction of Bmp7 in Hnf4a F/F;AlbERT2cre ϩ tamoxifen mice was associated with steatosis and liver damage or cellular proliferation, Bmp7 levels were measured in the Vhl F/F;AlbERT2cre mouse, which displays hepatic steatosis, inflammation, and fibrosis but not cellular proliferation (22).…”
Section: Loss Of Hnf4␣ Induces Hepatotrophic Factor Bone Morphogenetimentioning
confidence: 99%
“…The study protocol was approved by the Institutional Review Board of the National Health Research Institutes (Human Ethics Committee code EC0971102). RNA from these samples was reverse transcribed into complementary DNA (cDNA) for quantitative polymerase chain reaction (qPCR) analysis as described 21. The mRNA expression levels of MAN1A1 , MAN1A2 , MAN1B1 , and MAN1C1 were quantified using qPCR.…”
Section: Methodsmentioning
confidence: 99%
“…RNA extraction and reverse‐transcription qPCR were performed as described 21. The specific primers used for PCR amplification are shown in Supporting Table S5.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, gene expression profiling analysis has detected Spi-B in some malignant solid tumors including gastric cancer (13) and colorectal cancer (14). IHC staining also detected Spi-B in hepatocellular carcinoma (15,16), suggesting that Spi-B may be aberrantly expressed in some solid tumors. However, the functional consequence of Spi-B expression in carcinomas is completely unknown.…”
Section: Spi-b (Encoded By Spib) An Ets Family Transcription Factormentioning
confidence: 99%